2020
DOI: 10.1093/noajnl/vdaa067
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HGF/MET axis along with p53 inhibition induces de novo glioma formation in mice

Abstract: Abstract Background Aberrant MET receptor tyrosine kinase (RTK) activation leads to invasive tumor growth in different types of cancer. Overexpression of MET and its ligand hepatocyte growth factor (HGF) occurs more frequently in glioblastoma (GBM) than in low-grade gliomas. Although we have shown previously that HGF-autocrine activation predicts sensitivity to MET tyrosine kinase inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…During normal neurogenesis, neural stem cells (NSCs) are primarily located in the hippocampus and subventricular zone (SVZ) where they proliferate into multi-lineage progenitor cells and differentiate into neurons, astrocytes, and oligodendrocytes to populate the nervous system. 21 However, glioma stem cells (GSCs) may arise from normal NSCs or neural progenitor cells that harbor genetic alterations, such as amplifications and mutations, resulting in oncogene overexpression and leading to gliomagenesis. Early studies of EGFR signaling showed that neural progenitors from the adult SVZ respond to EGFR activation with enhanced proliferation and migration.…”
Section: Genetic Rtk Alteration and Gliomagenesismentioning
confidence: 99%
See 2 more Smart Citations
“…During normal neurogenesis, neural stem cells (NSCs) are primarily located in the hippocampus and subventricular zone (SVZ) where they proliferate into multi-lineage progenitor cells and differentiate into neurons, astrocytes, and oligodendrocytes to populate the nervous system. 21 However, glioma stem cells (GSCs) may arise from normal NSCs or neural progenitor cells that harbor genetic alterations, such as amplifications and mutations, resulting in oncogene overexpression and leading to gliomagenesis. Early studies of EGFR signaling showed that neural progenitors from the adult SVZ respond to EGFR activation with enhanced proliferation and migration.…”
Section: Genetic Rtk Alteration and Gliomagenesismentioning
confidence: 99%
“… 40 With MET RTK, Qin et al demonstrated that transgenic mice overexpressing the human HGF/MET axis along with p53 inhibition induced GBM in mice. 21 Moreover, in mice deficient in the tumor suppressor genes Ink4b and Arf irradiation-induced DNA damage triggered glioma formation with Met amplification as the most significant oncogenic event. 41 In all these 3 animal models, glioma arising from EGFR vIII or MET activation expressed GSC markers, supporting the concept that transforming NSCs into GSCs is critical to GBM development.…”
Section: Genetic Rtk Alteration and Gliomagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…SB has also been used to study RTK activity in gliomas; Qin et al. injected SB plasmids with HGF and MET cDNA as well as shRNA against p53 into lateral ventricles of neonatal mice and saw MET -driven glioma development ( 39 ). They tested two MET inhibitors, V-4084 and SGX523, and found sensitivity to both in isolated neurosphere cell lines.…”
Section: Genetically Engineered Mouse Models (Gemm)mentioning
confidence: 99%
“…HGF/MET overexpression frequently occur in GBM patients and is associated with poor prognosis [54,79,80]. Using a transgenic mouse model, Qin et al [81] showed that overexpression of HGF and MET may transform neuro stem cells into glioma stem cells (GSCs), leading to GBM initiation. GBM harboring MET amplification or HGF autocrine activation are sensitive to MET inhibitors in preclinical models [82,83], recent clinical trials further showed that a combination of MET and VEGF inhibitors (ontarzucimab plus bevacizumab vs. placebo plus bevacizumab) significantly improved progression free survival (PFS) and overall survival (OS) in the mesenchymal subtype of recurrent GBM patients with high tumor HGF expression [84].…”
Section: Metmentioning
confidence: 99%